Photographic production and social uses: organic photography of a UN peace mission (1957-1967) (Tempo e Argumento, 2022)
This article is a long time effort. Fabric in the folds of almost two decades of intense research in the archives of the United Nations (UN), the Brazilian Association of Members of the Suez Battalion (Abibs) and in the dozens of photographic collections that I had the opportunity to access and / or that were given to me graciously provided by the photographing soldiers of the Suez Mission. Here, we seek to discuss some aspects of the photographic practice undertaken in the context of the first UN-sponsored Peace Mission on the Arab-Israeli border, on the Sinai Peninsula (on the Palestinian-Israel border) between the years 1957 and 1967. In general, the photographic production of the soldiers became a special excitement for those amateur photographers. The preference for photographs emphasizes their multidisciplinary character and gives us a special opportunity to carry out a historical recall of the so-called Suez Mission from them. Suez's photographs are understood beyond mere memory of old people, but are perceived as a cultural mark of that past that brings us to the surface.
Keywords: Arab-Israel conflict; peace mission; ONU; war photography